A history of the problems of philosophy - Janet, Paul Alexandre René (Macmillan and co., limited, 1902)
vol. I. Introduction. pt. I. Psychology.--vol. II. pt. II. Ethics. pt. III. Metaphysics. pt. IV. Theodicy.